General social aspects in Baghdad through the book 'Nishwar AI-Muhadara' by AI-Tanukhi - Malouh, Ahmad Taleb; Karimipour, Hamid (Journal of Humanities & Social Sciences, 2025)
The book "Nishwar Al-Muhadara wa Akhbar Al-Mudhakara" by Al-Tanukhi is one of the distinguished historical books in which the author carefully recorded the various daily events that he witnessed and heard in Baghdad. He conveyed to us the various daily activities carried out by the people of Baghdad, including economic, cultural, social, and political activities, which gave us an idea and a historical glimpse of Baghdad during the third and fourth centuries AH / ninth and tenth centuries AD. Al-Tanukhi spent twenty years writing his book and published it in eleven volumes. The daily economic activities of agriculture, industry, and trade were truly important aspects of daily life for the people of Baghdad, as al-Tanukhi mentioned them in his narrative of events and what he heard and saw. His writings on public life were particularly important in historical writings, especially since Baghdad was the capital of the Abbasid Caliphate. His information constituted an important and candid source of information about the reality of that time. Studying economic life not only provides us with a historical overview of public life, but also insight into the most important agricultural products, the most important crafts and industries, and the transactions and agreements between the people of Baghdad.The research aimed, in its content, to provide a historical overview of aspects of public life for the people of Baghdad through al-Tanukhi's lectures. We followed a historical approach based on collecting scientific material from historical sources and critiquing and analyzing it to arrive at historical truth. Our research reached several results, which we mentioned in the conclusion and its summary: that there is a mutual influence between the public and the authorities that contributes to the nature of the course of historical events, regardless of their activities, especially economic ones.
Keywords: Baghdad; Nashwar lecture; economy; agriculture; industry; trade